2008
DOI: 10.1002/pmic.200800329
|View full text |Cite
|
Sign up to set email alerts
|

Application of electron transfer dissociation (ETD) for the analysis of posttranslational modifications

Abstract: Despite major advantages in the field of proteomics, the analysis of PTMs still poses a major challenge; thus far, preventing insights into the role and regulation of protein networks. Additionally, top-down sequencing of proteins is another powerful approach to reveal comprehensive information for biological function. A commonly used fragmentation technique in MS-based peptide sequencing is CID. As CID often fails in PTM-analysis and performs best on doubly-charged, short and middle-sized peptides, confident … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
178
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(180 citation statements)
references
References 73 publications
1
178
0
1
Order By: Relevance
“…In particular, this approach has the advantage of preserving unstable side-chain modifications during fragmentation [11,28]. Several different instrumental approaches have been developed to utilize electrons for fragmentation, including ECD in FT-ICR mass spectrometers [29], ECD in radio-frequency linear ion trap mass spectrometers [30], and electron-transfer ion/ion reactions in quadrupole/linear ion trap mass spectrometers [31], hybrid quadrupole-hexapole FT-ICRs [32], and hybrid linear ion trap-Orbitrap mass spectrometers [33].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, this approach has the advantage of preserving unstable side-chain modifications during fragmentation [11,28]. Several different instrumental approaches have been developed to utilize electrons for fragmentation, including ECD in FT-ICR mass spectrometers [29], ECD in radio-frequency linear ion trap mass spectrometers [30], and electron-transfer ion/ion reactions in quadrupole/linear ion trap mass spectrometers [31], hybrid quadrupole-hexapole FT-ICRs [32], and hybrid linear ion trap-Orbitrap mass spectrometers [33].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that attachment of an electron to multiply protonated phosphopeptides caused backbone fragmentations while preserving the phosphate group in the fragments [4]. This feature has been utilized in studies aimed at the localization of phosphorylated residues in peptides produced by enzymatic digestion of proteins [5][6][7][8][9][10][11][12]. However, it has also been reported that the presence of phosphorylated serine residues hampered backbone dissociations of several synthetic peptides [16].…”
Section: Introductionmentioning
confidence: 98%
“…E lectron-based methods such as electron capture dissociation (ECD) [1] and electron transfer dissociation (ETD) [2,3], which are collectively referred to as ExD, have been shown to be suitable for the analysis of peptides posttranslationally modified by phosphorylation [4][5][6][7][8][9][10][11][12], sulfation [13], or glycosylation [14,15]. It has been reported that attachment of an electron to multiply protonated phosphopeptides caused backbone fragmentations while preserving the phosphate group in the fragments [4].…”
Section: Introductionmentioning
confidence: 99%
“…Because of high ␣1(V) Pro content and decreased efficacy of ETD-induced cleavage of Pro N-C ␣ bonds, ETD MS 2 analyses occasionally did not provide sufficient numbers of sequenceinformative product ions to permit PTM localization (67). To complement ETD data, data were also acquired utilizing HCD collected at different collision energies.…”
Section: A High Mass Accuracy High Resolution Tandem Mass Spectrometmentioning
confidence: 99%